An Effective Paradigm for Selecting Channels in 6G Wireless Networks with Improved Quality of Service - Afzal, Humaira; Sajid, Kainat; Hameed, Muzaffar; Mufti, Muhammad Rafiq; Batool Gill, Humera (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Faster transmission of information and improvements to existing spectrum access procedures will define 6G wireless networks. The requirements of communication systems to serve the expanding demands for more services are critical because spectrum resources are quite limited. Due to the vast number of equipment, there is scarcely any spectrum left to offer future technologies. It provides access based on methods that use licensed spectrum to resolve spectrum crowding issues in 6G wireless networks and satisfy the future demands for wireless communications. This results in dynamic access, where licensed access must provide equitable allocation mechanisms that raise quality of service (QoS) while also posing minimum user interference. In this study, a channel selection algorithm for optimizing frequency, power, and penetration rate in a 6G communication system utilizing a technique that allocates frequency dynamically in a multi-user scenario is presented and evaluated. The proposed approach enables secondary users (SUs) to exchange relevant information prior to channel allocation so they can choose the channel with the highest probability of being available. A hybrid approach based on technique for order of preference by similarity to ideal solution (TOPSIS) and analytical hierarchy process (AHP) is used to perform evaluation and validation with the metrics of frequency usage, SU power consumption, and transmitted signal -penetration rate. Simulated outcomes show that the proposed productive channel allocation technique outperforms the traditional channel allocation strategies in terms of minimal frequency utilization, minimal power consumption, and minimal information loss.